2014
DOI: 10.1002/lary.24825
|View full text |Cite
|
Sign up to set email alerts
|

Changes in site of obstruction in obstructive sleep apnea patients according to sleep position: A DISE study

Abstract: When sleep posture is changed from supine to lateral, obstruction due to structures such as tongue base and larynx improves dramatically. Obstruction in lateral position is mostly due to obstruction at the oropharyngeal LWs. Therefore, position dependency is mostly determined by LW collapsibility. Evaluating the changes of the upper airway according to sleep position can further characterize the upper airway collapsibility and can be used for tailored treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 29 publications
3
59
1
Order By: Relevance
“…A number of recent studies on the pathogenesis of POSA have emphasized the gravity of respiratory events occurring in the supine position (Camacho et al, 2014;Joosten et al, 2014;Lee et al, 2015). In our study, siOSA presents with milder objective sleep parameters but poorer subjective sleep quality and mood; this result suggests the possibility that respiratory events occurring while in a supine position may be crucially detrimental to subjective sleep quality and mood, notwithstanding equivalent or milder obstructive features.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…A number of recent studies on the pathogenesis of POSA have emphasized the gravity of respiratory events occurring in the supine position (Camacho et al, 2014;Joosten et al, 2014;Lee et al, 2015). In our study, siOSA presents with milder objective sleep parameters but poorer subjective sleep quality and mood; this result suggests the possibility that respiratory events occurring while in a supine position may be crucially detrimental to subjective sleep quality and mood, notwithstanding equivalent or milder obstructive features.…”
Section: Discussioncontrasting
confidence: 42%
“…The POSA is a common form of the disease with milder clinical features compared with NPOSA (Oksenberg et al, 1997;Joosten et al, 2012). However, despite recent progress (Camacho et al, 2014;Lee et al, 2015), the mechanisms underlying POSA including its interaction with upper airway collapsibility, or reduced lung volume, are poorly understood (Joosten et al, 2014). Furthermore, despite recent studies suggestive of the effectiveness of positional therapy in POSA, its effectiveness depends on the severity of the disease (van Maanen et al, 2012Ravesloot et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…5 Lee et al performed DISE in 85 patients and reported a decrease in the prevalence of tongue base obstruction when moving from supine (71.1%) to lateral sleep (7.1%). 3 However, there are some methodological differences between this paper and our study. First, as a condition for tongue base obstruction, Lee and colleagues used the criteria of a 50% displacement compared to wakefulness.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies suggest that sleeping supine could affect the collapse of particular structures within the airway, such as the tongue base or epiglottis. [3][4][5] However, these studies lacked quantitative measurements of airway size and flow in the different sleeping positions, making it difficult to determine the effect size of positional changes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent DISE study examining the effect of sleep position found that the incidence of laryngeal obstruction dropped dramatically from 21.2 to 1.2% when the study participant was moved from supine to lateral position. In addition, lateral pharyngeal wall obstruction was found to become the most prominent pattern in the lateral decubitus position, exhibiting no positional dependency [21 ]. These findings imply that laryngeal obstruction, as a component of sleep apnoea, is mainly relevant in the supine position, and raises the potential role of lateral sleep positioning devices in the treatment of OSA with laryngeal obstruction.…”
Section: The Larynx As a Cause Of Airway Obstruction In Obstructive Smentioning
confidence: 94%